Medical Device-Associated Candida Infections in a Rural Tertiary Care Teaching Hospital of India - Sachin C. Deorukhkar; Santosh Saini (Interdisciplinary Perspectives on Infectious Diseases)
Health care associated infections (HCAIs) add incrementally to the morbidity, mortality, and cost expected of the patient’s underlying diseases alone. Approximately, about half all cases of HCAIs are associated with medical devices. As Candida medical device-associated infection is highly drug resistant and can lead to serious life-threatening complications, there is a need of continuous surveillance of these infections to initiate preventive and corrective measures. The present study was conducted at a rural tertiary care hospital of India with an aim to evaluate the rate of medical device-associated Candida infections. Three commonly encountered medical device-associated infections (MDAI), catheter-associated urinary tract infection (CA-UTI), intravascular catheter-related blood stream infections (CR-BSI), and ventilator-associated pneumonia (VAP), were targeted. The overall rate of MDAI in our hospital was 2.1 per 1000 device days. The rate of Candida related CA-UTI and CR-BSI was noted as 1.0 and 0.3, respectively. Untiring efforts taken by team members of Hospital Acquired Infection Control Committee along with maintenance of meticulous hygiene of the hospital and wards may explain the low MDAI rates in our institute. The present surveillance helped us for systematic generation of institutional data regarding MDAI with special reference to role of Candida spp.